2006
DOI: 10.1634/stemcells.2005-0370
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal Stem Cells Spontaneously Express Neural Proteins in Culture and Are Neurogenic after Transplantation

Abstract: Reports of neural transdifferentiation of mesenchymal stem cells (MSCs) suggest the possibility that these cells may serve as a source for stem cell-based regenerative medicine to treat neurological disorders. However, some recent studies controvert previous reports of MSC neurogenecity. In the current study, we evaluate the neural differentiation potential of mouse bone marrow-derived MSCs. Surprisingly, we found that MSCs spontaneously express certain neuronal phenotype markers in culture, in the absence of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
190
1
2

Year Published

2010
2010
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 294 publications
(212 citation statements)
references
References 53 publications
19
190
1
2
Order By: Relevance
“…Our observation of the migration and differentiation properties of young canine BMSCs was similar to those of previous studies in which murine BMSCs were engrafted into the lateral ventricle of the neonatal mouse brain [3,10]. We found that although most of BMSCs remained around the injection site, a small number of young canine BMSCs penetrated into the SVZ and assumed various morphologies resembling process-bearing neurons.…”
Section: Preparation Of Canine Bmscs and Fibroblastssupporting
confidence: 88%
See 1 more Smart Citation
“…Our observation of the migration and differentiation properties of young canine BMSCs was similar to those of previous studies in which murine BMSCs were engrafted into the lateral ventricle of the neonatal mouse brain [3,10]. We found that although most of BMSCs remained around the injection site, a small number of young canine BMSCs penetrated into the SVZ and assumed various morphologies resembling process-bearing neurons.…”
Section: Preparation Of Canine Bmscs and Fibroblastssupporting
confidence: 88%
“…Cell suspensions were made in PBS (2.0  10 5 /l) and transferred on ice to the mouse facility. DiI-labeled BMSCs or fibroblasts were transplanted into the left lateral ventricle of postnatal day-2 immunocompromised mice as described previously [3]. Under hypothermic anesthesia, 2.0  10 5 cells in 1 l of PBS were slowly injected into the left lateral ventricle, through a 30G needle attached to a 5 l Hamilton syringe.…”
Section: Preparation Of Canine Bmscs and Fibroblastsmentioning
confidence: 99%
“…10 It was originally hypothesized that regeneration occurs directly by incorporation of MSC-derived neurons and oligodendrocytes to restore damage. 22,23 However, there is now evidence to support that treatment with MSCs after hypoxic-ischemic encephalopathy results in enhanced endogenous cell proliferation and differentiation. In addition, MSC treatment may also be associated with the inhibition of injurious processes.…”
Section: Discussionmentioning
confidence: 99%
“…The sections were examined for evidence of necrosis, inflammation, neoplasia and architectural distortion and atrophy. Since, there is abundant information describing MSC survival and migration within the CNS [10,11], sections were not elsewise examined for engraftment of MSC.…”
Section: Histological Studiesmentioning
confidence: 99%
“…The above assertion is supported by three major facts: a) MSC can differentiate outside the mesenchymal lineage into neurological precursors [5,9,10], b) after infusion of MSC to animals with genetic or experimental neurological diseases, MSC migrate and survive within the central nervous system [6,11] and contribute to the improvement/recovery of pre-symptomatic motor functions [6,7,[11][12][13] and c) MSC secrete several growth factors and chemokines that may create a neuroprotective environment favorable for tissue sparing and axonal regeneration [14,15 ].…”
Section: Introductionmentioning
confidence: 99%